2020
DOI: 10.3390/agronomy10111745
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Properties of Potato (Solanum tuberosum L.) in Response to Ozone-Induced Oxidative Stress

Abstract: We investigated the changes in the physiological and biochemical properties of potato plants exposed to differing ozone (O3) concentrations (5 ppm, 10 ppm) and exposure times (2, 4, 8, 12, 16 min) to determine the safe dose that could be used in crop protection programs. We measured the gas exchange, relative chlorophyll content, chlorophyll fluorescence and total antioxidant capacity in potato leaves exposed to O3 fumigation. The fresh weight (FW) of the aboveground part of the plants and a visual assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A similar plant response to stress was observed in other crop species. For example, an increase in Ci with a concomitant decrease in Pn, gs, and E was observed in potato under stress conditions caused by plant exposure to ozone (O 3 ) [46] and spraying with hydrogen peroxide (H 2 O 2 ) [47].…”
Section: Discussionmentioning
confidence: 99%
“…A similar plant response to stress was observed in other crop species. For example, an increase in Ci with a concomitant decrease in Pn, gs, and E was observed in potato under stress conditions caused by plant exposure to ozone (O 3 ) [46] and spraying with hydrogen peroxide (H 2 O 2 ) [47].…”
Section: Discussionmentioning
confidence: 99%
“…(2020) 34 found that sorrel plants had greater antioxidant potential after 1 mg/L ozone treatment, while 5 mg/L ozone treatment for a short time could also increase the antioxidant activity of potato leaves 35 . In this paper, lowconcentration ozone water irrigation and spraying could significantly increase the antioxidant enzyme activity of tomato leaves, in accordance with the above research 34 .…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in SOD and glutathione reductase (GR) activities between the genotypes or O 3 treatments ( Chutteang et al., 2016 ). Similarly, Szpunar-Krok et al. (2020) tested the effects of two doses of O 3 (5 and 10 ppm), different exposure times (2, 4, 8, 12, and 16 min), and two application periods (21 and 28 d after sowing) on potatoes ( Solanum tuberosum L.).…”
Section: Ozone As a Prooxidant And O 3 -Induced Ox...mentioning
confidence: 99%